2020
DOI: 10.1016/j.semarthrit.2020.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability, validity, and responsiveness of the multi-biomarker disease activity score in patients with rheumatoid arthritis initiating methotrexate

Abstract: Background/Objective: We assessed the predictive value, validity, and responsiveness of the multi-biomarker disease activity (MBDA) score in rheumatoid arthritis (RA) patients initiating methotrexate. Methods:We examined data from a 16-week, open-label study of methotrexate in RA. Disease activity was assessed and the MBDA score was calculated using serum that was collected and banked from baseline and week 16. Multivariable logistic regression models assessed whether MBDA scores predicted treatment response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In a 2019 update of ACR guidance for measures of disease activity in patients with RA, the DAS28‐ESR and CDAI both achieved a consensus recommendation for preferred use in clinical practice. Although this is a report from a clinical trial, our results are consistent with the recent ACR guidance recommending the DAS28‐ESR and CDAI for use in measuring disease activity in clinical practice and with results of other RA treatments with different mechanisms of action (13–15). The reasons underlying our study's finding that the MBDA was not reliably responsive to changes in RA disease activity with multiple therapies are unclear.…”
Section: Discussionsupporting
confidence: 88%
“…In a 2019 update of ACR guidance for measures of disease activity in patients with RA, the DAS28‐ESR and CDAI both achieved a consensus recommendation for preferred use in clinical practice. Although this is a report from a clinical trial, our results are consistent with the recent ACR guidance recommending the DAS28‐ESR and CDAI for use in measuring disease activity in clinical practice and with results of other RA treatments with different mechanisms of action (13–15). The reasons underlying our study's finding that the MBDA was not reliably responsive to changes in RA disease activity with multiple therapies are unclear.…”
Section: Discussionsupporting
confidence: 88%
“…48 MBDA correlated with disease activity but not response to treatment. 28 The lack of prediction of MBDA to response to treatment was also previously demonstrated. 49 However, the response to treatment to be detected by a biomarker depends on the spectrum of disease activity from the peak to the point of remission.…”
Section: Discussionmentioning
confidence: 75%
“…27 Luedders B, et al, have shown that although the multibiomarker disease activity (MBDA) score moderately correlated with disease activity, it did not predict treatment response to methotrexate. 28 Another study by Baker J et al, demonstrated that adjusted and unadjusted MBDA score correlated similarly with clinical disease activity. Adjustment for leptin reduced the influence of adiposity, particularly among women but significantly estimated higher disease activity in thin men and women.…”
Section: Resultsmentioning
confidence: 97%
“…Patients excluded from the study included: patients with other rheumatic diseases (i.e., Sjogren's, SLE, and overlap connective tissue disease), pregnant or lactating women, women of childbearing age not practicing an effective method of contraception, patients with a history of alcohol abuse who are unwilling to abstain or limit alcohol consumption, and patients with cytopenias or abnormal hepatic or renal function at the time of screening. Healthy control plasma samples were collected from volunteers reporting well to excellent health [52]. All patients provided informed consent and the studies were conducted under the University of Nebraska Medical Center Institutional Review Board approved protocols.…”
Section: Patientsmentioning
confidence: 99%